The Effectiveness of Using Short Story to Improve Students’ Ability in Reading English Texts: Experimental Study at the Eight Grade Students of MTs. AL-Madani Pelulan in Academic - Jumatriadi Jumatriadi (LP2M STIT Palapa Nusantara, 2018)
This research is aimed at finding out the improving students’ ability in reading texts by using short story at the eight grade students of MTs. AL-Madani Pelulan The kind of the research is an experimental research. The population of this research is 54 students of the eight grade students of MTs. ALMadani Pelulan in which all of it as sample and divided into two groups that are XIIIA as experimental group and XIIIB as control group. The experimental group is taught by using short story as instrument and the control group is taught without short story or based on real object. The techniques of collecting data use multiple choise. The data collected were analyzed statistically by using t-test formula. The result of statistical analysis of t-test it was 3,13 which was higher than the critical value of t-table, it was 2,006 (0.05) and 1,675 (0.01). It means that t-test is higher than ttable in 0.05% of significance level and 52 of degree of freedom. Thus, it can concluded that the use of short story as media to improve students’ ability in reading text is enough interesting to apply in teaching reading texts. It means the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.